Oroantral communication: A surgical complication. Review - Vásquez-Villafane, Ana-Silvia (2017)
Oralantral comunication is a surgical complication that manifests itself with the connection of the oral cavity and the maxillary sinus . Its etiology is related multiple factors. For its diagnosis and treatment it is necessary evaluate clinical caracteristics like the symtoms associated with the oralantral communication, onset and the size it manifests itself. If the oralantral comunication is not corrected , inflamatory and infectuos conditions can occur in the maxillary sinus .